Risks of investment in personnel development: evidence from Ukrainian IT companies - Domkina, Oksana (Ekonomia Międzynarodowa, 2015)
In this paper, we examine key factors that influence the risks of investment in the development of human capital of a firm in the IT sector and estimate their weight in the overall risk. In particular, we single out the risk of premature voluntary termination of an employee, the risk of ineffective training, and the risk of a firm’s incorrect employee development strategy. Moreover, to support management of the mentioned kinds of risks, we enumerate the factors that influence them and classify those factors into three main groups: related to the employee, related to the firm, and related to the external environment. Based on this division, we build a model for estimating the risks of investing in the development of personnel using the Analytic Hierarchy Process (AHP).